Quadrupel Bilangan Bulat (a,b,c,d) yang Memenuhi a^2+b^2+c^2=d^2 - Qodriyah Qoyyim; Media Rosha (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — An integer if it satisfies the Pythagorean theorem is called a “Triple Pythagoras” where there is already a building formula from Euclides to determine integers and that .The next problem is how to construct the formula to determine the integers of quadruple and that satisfy This research is a theoretical research based on literature study. The purpose of this research is to determine the formula of integer’s quadruple and that satisfy and to determine the form that has been obtained. The formula by the first way is obtained , , , with terms is an odd integer, not a prime number, and are factor from which is The formula by the second way is with terms and are member of sets 5, 13, 17, 25, 29, … also applies to it multiplies. Thus formula by the first way obtained (4,7,4,9), (4,13,16,21), etc. And formula by the second way obtained (3,4,12,13), (9,12,8,17), etc. Keywords — Integer, Pythagorean Triple, Euclides' Formulas, Integer’s Quadruple.